Is Parental Divorce Homogamy Associated With a Higher Risk of Separation From Cohabitation and Marriage? - Kailaheimo-Lönnqvist Sanna; Fasang Anette; Jalovaara Marika; Struffolino Emanuela (Duke University Press, 2022)
Numerous studies have shown that parental divorce is associated with an increase in adult children's divorce risk. We extend this literature by assessing how parental divorce on both sides of a couple is related to their partnership dynamics, specifically, whether there is parental divorce homogamy and whether a history of parental divorce for both partners is associated with increased dissolution risks for cohabiting and married unions. We use Finnish Census Panel data on 28,021 cohabiting and marital partnerships to conduct event-history models that follow individuals between ages 18 and 45. Findings show substantial parental divorce homogamy. Children with experience of parental divorce have 13% greater odds of cohabiting with and 17% greater odds of marrying a fellow child of divorcees, compared with those whose parents have not divorced. Moreover, contrary to evidence from the United States and Norway, our findings for Finland support an additive—rather than multiplicative—association between parental divorce homogamy and union dissolution. Parental divorce homogamy increases offspring's union dissolution risk by 20% for cohabitation and 70% for marriage, compared with couples for whom neither partner's parents are divorced. In Finland, the sizes of these associations are notably weaker than in the United States and Norway, likely because cohabitation and separation are more widespread and socially accepted in Finland, and an expansive welfare state buffers the socioeconomic consequences of divorce.